Organizational Learning Process, CEO Values and Sustainability Performance of Manufacturing Firms in Uganda - Lwanga, Freddie; Korir, Micheal; Bonuke , Ronald (SEISENSE (PRIVATE) LIMITED, 2023)
Purpose- The paper aims to examine the moderating effect of CEO personal values on the relationship between the organizational learning process and sustainability performance.Design/Methodology- An explanatory cross-sectional design was used to obtain quantitative data from the managerial staff of 256 medium and large manufacturing firms in Uganda. A survey instrument was used to collect data.Findings- Organizational learning process and the CEO's personal values have a significant positive direct effect on sustainability performance. Further, the CEO's personal values significantly moderate the relationship between the organizational learning process and sustainability performance.Practical Implications- Strategies such as training, teamwork, consultancy engagements, and research facilitate learning processes of knowledge acquisition, sharing, interpretation, and storage which in turn improve sustainability performance. In addition, firms that hire CEOs whose personal value system is inclined towards change and self-transcendence are more likely to foster a culture of continuous organizational learning which improves sustainability performance